2005
DOI: 10.1176/appi.ps.56.10.1274
|View full text |Cite
|
Sign up to set email alerts
|

Special Section on Relapse Prevention: Substance Abuse Relapse and Factors Associated With Relapse in an Inner-City Sample of Patients With Dual Diagnoses

Abstract: Age, therapeutic residential programming, and, to a lesser degree, employment appear to be potential factors to consider in the development of relapse prevention models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
4
28
1
Order By: Relevance
“…Relapse into substance abuse has been correlated with social factors such as poor housing status, limited social support, and lack of drug treatment (Mayer et al, 1993), and with reports of family fights or drug use among family members or spouses (Ellis et al, 2004). Conversely, continued remission or successful recovery has been associated with older age and with living in residential treatment programs (Rollins et al, 2005), with reports of families getting along (Ellis et al, 2004), and with other measures of positive social support within local or family networks (Barber & Crisp, 1995;McMahon, 2001;Flynn et al, 2003;Granfield & Cloud, 2001). The concept of recovery capital (Cloud & Granfield, 2001, in fact, explicitly encompasses both the individual and the social levels.…”
Section: Finding Funding and Developing A Theoretical Approachmentioning
confidence: 99%
“…Relapse into substance abuse has been correlated with social factors such as poor housing status, limited social support, and lack of drug treatment (Mayer et al, 1993), and with reports of family fights or drug use among family members or spouses (Ellis et al, 2004). Conversely, continued remission or successful recovery has been associated with older age and with living in residential treatment programs (Rollins et al, 2005), with reports of families getting along (Ellis et al, 2004), and with other measures of positive social support within local or family networks (Barber & Crisp, 1995;McMahon, 2001;Flynn et al, 2003;Granfield & Cloud, 2001). The concept of recovery capital (Cloud & Granfield, 2001, in fact, explicitly encompasses both the individual and the social levels.…”
Section: Finding Funding and Developing A Theoretical Approachmentioning
confidence: 99%
“…The clustering of charges in the younger age cohorts suggests that these individuals may have peers who use drugs or frequent settings where drugs are easily obtained. As we noted, this should not come as a surprise, given the drug-in-fested environments in which some persons with mental illness reside and the lifestyle patterns these environments may induce (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 84%
“…One pathway to exposure may be linked with the poverty experienced by persons with serious mental illness, which forces them to reside in locales with high rates of criminal activity and, in particular, high rates of illicit drug activity (11). In such areas, as has been well documented, the social networks in which individuals participate may be ones in which pressure to buy and use drugs is high; also, in these areas persons receiving disability payments may be attractive and easy targets for drug dealers (12)(13)(14)(15)). …”
mentioning
confidence: 99%
“…On the other hand, there is evidence that attaining abstinence reduces the negative outcomes of substance use in individuals with SMI [57][58][59]. Higher scores for social competence have been reported in abstainers in another study [39].…”
Section: Discussionmentioning
confidence: 90%
“…One ethnographic study [37] and one self-reported study [38] have examined participants' reasons for quitting and have shown that supportive networks are influential in encouraging sobriety. Findings from studies using various research designs have indicated that meaningful activities and a safe living environment are important to abstinence from substance use in individuals with SMI [33,39,40]. In a 2010 study of patients' perspectives on their reasons for cannabis use, Asher and Gask [41] identified five reasons to abstain: disliking the effect and illegality of cannabis, financial benefits of abstaining, negative impact on physical and mental health, increased family support and hoping to develop relationships, and hopes for improved occupational and accommodation status.…”
Section: Introductionmentioning
confidence: 99%